Fake snakes and weird wizards - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2015)
"Hank's sister Emily wants Ralph's Reptile Show to perform at her birthday party more than anything, but Ralph is booked solid. So Hank comes up with a plan: he'll disguise himself as a magician called The Westside Wizard and pull a snake from thin air! But when Hank's true identity is revealed during his performance, his good deed might just turn into a huge disaster"--